The Role of Virtual Laboratories in Improving Contextual Numeracy Skills in Physics Experiment - Almira Erika Putri; Rindi Sartika Dwi Oktari; Febby Apriani; Gunawan Gunawan; Nina Nisrina (Indonesian Journal of Teacher Education, 2023)
The development of digital technology encourages the use of virtual laboratories as an alternative in physics learning. This study aims to examine the role of virtual laboratories in helping improve students' contextual numeracy skills when conducting physics experiments. The method used is a literature study by analyzing various related scientific sources, such as domestic and international journals, which discuss the use of virtual laboratories and numeracy skills in the physics teaching and learning process. The results of the study indicate that virtual laboratories can improve students' critical thinking skills through the presentation of interactive simulations that allow students to conduct experiments, observe phenomena, and analyze numerical data more flexibly. In addition, the use of virtual laboratories has been proven to help increase student participation, critical thinking skills, and a better understanding of physics concepts. Incorporating simulations in learning helps students connect mathematical concepts with real physics situations and strengthens quantitative thinking skills when solving problems. Thus, it can be concluded that virtual laboratories are an effective learning method in helping improve students' contextual numeracy skills when conducting physics experiments.